PERANCANGAN SISTEM INFORMASI PEMESANAN TIKET TRAVEL BERBASIS WEB DENGAN METODE WATERFALL - Mulyana, Wide; Barokah, Citra Khairiyatul; Adrian, Muhammad (Politeknik Caltex Riau, 2025)
PT Randu Delia Wisata is a transportation service company that still manages its business processes, such as ticket booking, fleet management, and transaction reporting, manually, leading to recording errors, data redundancy, and service delays. This study aims to design a web-based travel ticket booking information system to improve operational efficiency and service quality. The development process uses the Waterfall model, which includes stages of requirements analysis, system design using UML and ERD, implementation with PHP and MySQL, and functional testing using Blackbox Testing. The results produce a web-based application design that integrates customer data management, ticket booking, departure scheduling, and automated transaction reporting. The system is designed with an interface that is easy to use by customers, administrators, and company owners. Based on implementation and testing results, the system improves data accuracy, accelerates service processes, and supports faster and more reliable managerial information delivery. The implementation of this system is expected to optimize PT Randu Delia Wisata’s services and serve as an initial step toward the digitalization of business processes in the transportation sector.